Evaluation of color stability on resin composite specimens using different polishing kits: an in vitro study - Alghamdi, Hamed S.; Alosaimi, Hanan Z.; Kaki, Demah E.; Majrashi, Amani H.; Rassas, Ayah I.; AlHumaid, Ghena; Alshehri, Turki; Balhaddad, Abdulrahman A.; Barashi, Mohammed A.; Alsahafi, Rashed A.; Alhazmi, Hesham A. (Frontiers in Dental Medicine, 2025)
ObjectivesModern dentistry has introduced color-matching restorations along with commercial finishing/polishing kits to improve color stability. This study aims to evaluate the effect of three finishing and polishing kits on the color stability of Filtek™ Z250 resin composite.MethodsThis study involved 140 resin composite discs categorized into three experimental groups: Sof-Lex, Super-Snap, and OptiDisc (40 discs each), along with a control group of 20 discs. Each disc was exposed to either coffee or cola after finishing or following both finishing and polishing. Mean color change was computed for each group. A One-Way ANOVA was conducted to compare mean color changes among the finishing kits.ResultsSuper-Snap demonstrated the highest color stability among different finishing kits for Filtek™ Z250 resin composites in coffee staining, with a mean color change of 10.7. After finishing and polishing, its color stability improved to 10.2. For cola staining, Super-Snap had a mean color stability of 2.98, which decreased to 2.07 after polishing. However, there were no significant differences between the kits (p > 0.05). Furthermore, immersion in coffee resulted in significantly greater color changes compared to cola for all tested groups (p < 0.05).ConclusionThe three multi-step finishing and polishing kits for Filtek™ Z250 demonstrated similar color stability, with coffee showing a higher staining potential than cola. Patients with anterior composite restorations may require education about the risk of staining and the importance of dental follow-ups to maintain the aesthetic quality of their restorations.